Trimodality Image Registration of Ultrasound, Cardiac Computed Tomography, and Magnetic Resonance Imaging For Transcatheter Aortic Valve Implantation and Replacement Image Guidance - Aisyah Rahimi; Azira Khalil; Aminatul Saadiah Abdul Jamil; Khin Wee Lai; Amir Faisal; Shahrina Ismail; Muhammad Mokhzaini Azizan (Springer Nature, 2024)
Indexed by WOS/Scopus/ERA